A hybrid deep learning model and explainable AI-based Bengali hate speech multi-label classification and interpretation - Shakil, Mahmudul Hasan (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Science in Computer Science and Engineering, 2022.